TRADITIONAL AND MODERN IN THE MASS CONSCIOUSNESS STRUCTURE (IN THE CONTEXT OF INTER-CIVILIZATIONAL CHALLENGES) - Sidorkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Mass consciousness has a complex structure that includes stable and dynamic components, different levels, and a certain direction of its development processes. Social practice acquired distinct features of intercultural interaction in the conditions of inter-civilizational challenges. The aggravation of the conflict phases of these processes makes their retrospective analysis relevant, in particular through the concept of age conflict. The aim and tasks are an analysis of the structure of modern mass consciousness, and the ratio of different worldview elements in its composition in the context of modern inter-civilizational challenges. Research methods are primarily the dialectical approach in interpreting the interaction of levels and forms of social consciousness, including the relationship between consciousness and being. The dialectical approach was complemented by the civilizational approach, in particular when analyzing issues in the context of age conflicts. Research results. The structure of modern mass consciousness is characterized by a certain dynamism and demonstrates a change in the forms of its manifestation. In Ukrainian society, in the structure of the mass everyday consciousness, several components are represented as certain «mental formations». Іntercivilizational interaction took on the features of a social conflict as an acute phase of the development of certain age-old conflicts that arose in the past and developed over many decades. Discussion. These features of the structure of modern mass social consciousness are due to a number of reasons related to the spread of values of industrial civilization with its secularization, the development of urban structures, scientific and technological progress, and rationalism. At the root of age-old conflicts is the struggle of social systems, in particular, their political systems or ideological doctrines, which is also manifested in the field of international relations. Age conflicts can be of different natures: inter-formational and intra-formational, internal (civil conflicts), and external (interstate). Conclusion. The dynamism of the modern mass everyday consciousness is manifested by several components as certain «mental formations» in its structure. The current socioeconomic and political situation in Ukrainian society contributes into the activation of various non-traditional religious movements, the formation of ideologemes associated with different value orientations, and acting as the leading ideological dominants of mass consciousness. Familiarization with the historical features of the course of age-old conflicts in the inter-civilizational context shows the relevance of analyzing these issues in order to find ways to peacefully resolve such conflicts, which will be an important step on the way from inter-civilizational confrontation to cooperation between peoples and countries.